Revisiting the multiple roles of T-cadherin in health and disease - K.A. Rubina (Elsevier, 2021)
As a non-canonical member of cadherin superfamily, T-cadherin was initially described as a molecule involved in homophilic recognition in the nervous and vascular systems. The ensuing decades clearly demonstrated that T-cadherin is a remarkably multifunctional molecule. It was validated as a bona fide receptor for both: LDL exerting adverse atherogenic action and adiponectin mediating many protective metabolic and cardiovascular effects. Motivated by the latest progress and accumulated data unmasking important roles of T-cadherin in blood vessel function and tissue regeneration, here we revisit the original function of T-cadherin as a guidance receptor for the growing axons and blood vessels, consider the recent data on T-cadherin-induced exosomes’ biogenesis and their role in myocardial regeneration and revascularization. The review expands upon T-cadherin contribution to mesenchymal stem/stromal cell compartment in adipose tissue. We also dwell upon T-cadherin polymorphisms (SNP) and their possible therapeutic applications. Furthermore, we scrutinize the molecular hub of insulin and adiponectin receptors (AdipoR1 and AdipoR2) conveying signals to their downstream targets in quest for defining a putative place of T-cadherin in this molecular circuitry.